Postoperative outcomes in patients with COPD undergoing elective non-cardiac surgery: a propensity score-matched cohort study - Berikashvili, Levan B.; Shemetova, Mariya M.; Yadgarov, Mikhail Ya; Kadantseva, Kristina K.; Polyakov, Petr A.; Yakovlev, Alexey A.; Yavorovskiy, Andrey G.; Likhvantsev, Valery V. (Frontiers in Medicine, 2025)
BackgroundGiven the nature and pathophysiology of chronic obstructive pulmonary disease (COPD), it is reasonable to hypothesize that concomitant COPD may adversely affect clinical outcomes, leading to higher incidence of respiratory infections, prolonged mechanical ventilation, and prolonged hospital stay. However, robust evidence to support this assumption remains limited. The objective of this study was to evaluate the impact of chronic obstructive pulmonary disease (COPD) on postoperative outcomes in adult patients undergoing elective non-cardiac surgery.MethodsThis retrospective cohort study analyzed data from the eICU Collaborative Research Database (eICU-CRD), including adult patients admitted to the ICU following elective non-cardiac surgery. Propensity score matching (PSM) was performed to adjust for confounding variables between COPD and non-COPD groups. Matching was based on age, sex, BMI, APACHE IV score, surgery type, and comorbidities. Post-matching outcomes included mortality, ICU/hospital length of stay, need for mechanical ventilation (MV), and postoperative lab parameters.ResultsA total of 15,429 patients were included, with 1,720 (11.1%) having COPD. After PSM, 563 patients remained in each group. No significant differences were found in hospital (4.6% vs. 5.5%, p = 0.6) or ICU mortality (1.8% vs. 3.6%, p = 0.09). COPD patients had longer hospital stays (mean difference 1 day, p = 0.03) and a higher incidence of MV (35.9% vs. 27.7%, p = 0.003).ConclusionPatients with chronic obstructive pulmonary disease (COPD) undergoing surgery demonstrate comparable ICU and hospital mortality rates to those without COPD. However, they tend to experience a longer hospital stay and require prolonged mechanical ventilation postoperatively.